Leader Humility, Sense of Power, and Interpersonal Deviance Relationship Model in the Bureaucratic Culture - Hadmar, Ambo Sakka; Hendryadi, Hendryadi; Suratna, Suratna; Karyatun, Subur (Frontiers in Sociology, 2022)
Purpose Drawing on the approach—inhibition theory of power and the containment theory of control—we propose a relationship model of leader humility, sense of power, and interpersonal deviance, by placing bureaucratic culture as a boundary condition. Design/Methodology/Approach Using a moderated mediation model, this study applies hierarchical regression and bootstrapping analyses to data obtained from online questionnaire responses of 428 employees from various sectors in Indonesia. Findings The results reveal a positive relationship between leader humility and employees perceptions of the sense of power, as well as between the sense of power to interpersonal deviance. In addition, we confirmed the mediating role of the sense of power on the relationship between leader humility and interpersonal deviant. Bureaucratic culture has been confirmed to moderate the relationship between a sense of power and interpersonal deviance. Practical Implications Companies can provide leadership training to leaders to convey to them when and where to demonstrate humility. Furthermore, the effectiveness of leaders' humility can be increased and their sense of power and interpersonal deviance reduced if the company adopts a low-level bureaucratic culture. Originality/Value The current study contributes to the extant literature by revealing the moderating effects of bureaucratic culture on the relationship between the sense of power and interpersonal deviance, clarifying how, and when employees' sense of power stimulates interpersonal deviance in the Asian context.